Rural sector reform and internet adoption in NGOs: The case of Indonesia - Yanuar Nugroho (The University of Manchester, Manchester Business School, 2008)
Today rural sector reform is a paramount issue in Indonesian development. Yet, different social actors have different perspectives and stances towards it. Non-Government Organisations (NGOs) in Indonesia have established themselves in pivotal positions in the social, economic and political landscape across the country, and a large number of their works has often been connected with development in rural sector. But, little has been studied to understand how NGOs in Indonesia, particularly rural NGOs, engage with the issue of rural development itself. With the rural development being one of the oldest issues widely discussed among activists since the early days of the Indonesian NGOs, it is interesting to see how they understand the rural sector reform issue today. An empirical study was conducted recently to see how some Indonesian NGOs, in their endeavour to respond and broaden the discourse, utilise Internet technology. The study employs combination of quantitative and qualitative approach to build a detailed story about how different organisations working in the rural sector reform issue deploy strategies to deal with the issue. By so doing, it aspires to contribute to the advancement of theory relating to the efficacy of Internet as a tool for social reform and development. Two related issues are at stakes. First, amidst everything else, for most NGOs working in rural sector reform, technology is not seen as a compelling issue. Second, the study finds that there is a real need for a further thinking and reflection focusing on what can actually be done with the strategic implementation of the Internet within organisations working in rural issues generally.
Keywords: 330; internet adoption; Indonesia; non-governmental organisations; rural sector reform; rural sector development; Nichtregierungsorganisation; Internet; Verhalten in Organisationen; Ländliche Wirtschaft; Ländliche Entwicklung; Indonesien